2001
DOI: 10.1007/bf03174447
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between playfulness and creativity of Japanese preschool children

Abstract: The purpose ofthis study was to examine the relationship between playfulness and creativity of164 Japanese children agedfive and six in a group-oriented program. Playfulness was assessed using The Child Behaviors Inventory, teacher interviews, and observations. Creativity was measured using The Creativity Thinking-Drawing Production Test, The Drawing Test, teacher interviews, and observations. Although the statistical data analysis indicated no significant relationship between playfulness and creativity, the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Interestingly, Japanese teachers also noted the concept of internal playfulness, while their American counterparts did not mention this subject. In a previous study, Taylor (1992) found that Japanese educators considered that although some children may be quiet and do not appear to be overtly playful, it does not mean that they are not playful. These children may be observing others' playful behaviors and considering their play for the next day (Taylor, 1992).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, Japanese teachers also noted the concept of internal playfulness, while their American counterparts did not mention this subject. In a previous study, Taylor (1992) found that Japanese educators considered that although some children may be quiet and do not appear to be overtly playful, it does not mean that they are not playful. These children may be observing others' playful behaviors and considering their play for the next day (Taylor, 1992).…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study, Taylor (1992) found that Japanese educators considered that although some children may be quiet and do not appear to be overtly playful, it does not mean that they are not playful. These children may be observing others' playful behaviors and considering their play for the next day (Taylor, 1992). One early childhood educator's comments might explain this internal playfulness: "Studies on play and playfulness in western countries tend to focus on external behavior ... we may need to go beyond that to understand children's playfulness.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of research of George (2016) reveal that there is a significant influence of brain storming on total creativity scores, verbal creativity, verbal elaboration and verbal originality scores. In the research of Taylor and Rogers (2001), the qualitative data analysis revealed that such a relationship may exist between playfulness and creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability Some indications of reliability are retrievable here: Validity Some indications of validity are retrievable here: Training Greek ; Japanese (Taylor & Rogers, 2001) Context Psychology…”
Section: Normative Sample Data Not Availablementioning
confidence: 99%